Docking e atividade antinociceptiva orofacial do geraniol em camundongos - Costa, Tereza Karla Vieira Lopes da (2018)
Geraniol is the monoterpene alcohol, found in the essential oils of several aromatic plants. It has a broad aspect of pharmacological activities, with emphasis on antinociceptive activity. The presente study was characterized as non-clinical, randomized, controlled and double-blind. Its objective was to evaluate the orofacial antinociceptive effect of geraniol in an experimental model of nociception in mice and and its molecular anchorage mechanism. For each test performed, seven animals per group were treated through the intraperitoneal route (i.p.) with geraniol according to their dose (12.5; 25 and 50mg / kg, ip), with the positive control (morphine-6mg / kg, ip) and the negative control (saline + 0.2% Tween 80, ip), by a researcher 30 minutes before the beginning of the experiment. Nociception induction was carried out by injecting the agents glutamate (40 µl, 25 µM), capsaicin (20 µl, 2.5 µg) and formalin (20 µl, 2%) in the upper right lip (perinasal) region of the animal. The behavioral analysis of the animals considered the friction time, in seconds, of the mentioned region using hind or front paws by a researcher blind to the treatment groups. The statistical analysis was performed blindly, considering α = 5%. To identify whether there was a statistically significant difference between the groups, the ANOVA test of a single factor was implemented. They were compared utilizing the unpaired T-test of heterogeneous variances. The results of the glutamate and capsaicin test established antinociceptive activity (p <0.005 and power> 80%) at 25 mg/kg and 50 mg/kg. In the formalin test, geraniol reduced nociception at the concentration of 50 mg/kg (p <0.005 and power> 80%). The study of molecular anchorage observed high values of binding between the evaluated substances and receptors: metabotropic receptor for glutamate six (mGlur6); Nmethyl-D-aspartate (NMDA); α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA); opioid mü (μ) receptor; opioid kappa (ĸ) receptor; opioid delta (δ) receptor; vanilloid transient potential receptor one (TRPV1). From the data analysis, it can be inferred that geraniol demonstrated significant therapeutic potential in combating orofacial pain.